The Influence of a Training Program on Situational Social Skills of Sport-Exercising Schoolchildren - Malinauskas, Romualdas; Šniras, Šarūnas (Acta Paedagogica Vilnensia, 2006)
The problem of the study is that data, which would reveal the influence of a training program on the situational social skills among sport-exercising schoolchildren, is still lacking. The purpose of this study is to define the evolution of situational social skills among sport-exercising schoolchildren under the influence of educational training program. It is presumed that after the training program situational social skills among sport-exercising schoolchildren are higher. The study employed the E. Gambrill (1995) adapted questionnaire containing 12 situational skills. The following social skills were estimated: to be able to refuse, to react to remarks, to be able to contradict, to apologise, to recognise of being wrong, to be able to enjoy praise, to start a conversation, to be able to talk, to be able to end a conversation, to ask for help, to say good words, to tell what one feels. The skills training experiment based on the principle of random serial selection was carried out with an experimental group of 26 sport-exercising schoolchildren and a control group of 28 sport-exercising schoolchildren (in total, 54 tested persons). Both tested groups consisted of youth sport-exercising schoolchildren attending Kaunas V. Chomicius basketball school who were born in 1991. A repeated research after the training experiment disclosed that measures of influence applied during the experiment had impact on the level of situational social skills. It was established that variations of situational social skills in the control group were small, and the rates of the experimental group statistically significantly increased due to a considerable increase of responses in which the level of these skills was evaluated as high. The analysis of results showed that significantly higher were evaluated the following situational social skills: ability to refuse, to react to remarks, to contradict, to apologise, to recognise of being wrong, to start a conversation, to be able to talk, to end a conversation, to ask for help, to say good words, to tell what one feels. It is believed that considerable change in the assessments of situational social skills in the experimental group are significant because in this case they were based not on the data of schoolchildren’s self-assessment, but on an objective opinion of team members. It is stated that changes that took place in the situational social skills of the experimental group might be directly related to the impact of the program for social skills training. After the experiment the level of all the situational social skills of schoolchildren in the experimental group considerably increased.
Keywords: situational social skills training program; sport-exercising schoolchildren